SELECTION OF PROJECTS FOR FINANCING ON THE BASIS COMPLEX OBJECT «PROJECT – ORGANIZATION» COMPETITIVENESS ASSESSMENT - O. Afanasieva; A. Kovalev; V. Kovalev (Вестник университета)
The issues of system approach development to the selection process of projects proposed for financing and the construction of their rating score have been studied. This approach is a practical tool to justify the decision to support or reject projects. An interconnected system of functional tasks for assessing the competitiveness of a complex project-organization object and the direction of such an assessment have been proposed been proposed. The presented mathematics will allow take into account both various parameters of both the project itself and the features of the organization that plans to implement it. Such approach encourages these organizations, to increase their competitiveness. Based on the calculated ratings of complex objects there is their ranking. As a formalized means a matrix for the formation of decisions on the allocation of funds to the applicant organization to finance the declared project has been adduced.